Increasing ICU capacity to accommodate higher demand during the COVID‐19 pandemic. Issue 11 (22nd October 2021) - Litton, Edward; Huckson, Sue; Chavan, Shaila; Bucci, Tamara; Holley, Anthony; Everest, Evan; Kelly, Sean; McGloughlin, Steven; Millar, Johnny; Nguyen, Nhi; Nicholls, Mark; Secombe, Paule; et al.
Abstract: Objectives: To describe the short term ability of Australian intensive care units (ICUs) to increase capacity in response to heightened demand caused by the COVID‐19 pandemic. Design: Survey of ICU directors or delegated senior clinicians (disseminated 30 August 2021), supplemented by Australian and New Zealand Intensive Care Society (ANZICS) registry data. Setting: All 194 public and private Australian ICUs. Main outcome measures: Numbers of currently available and potentially available ICU beds in case of a surge; available levels of ICU‐relevant equipment and staff. Results: All 194 ICUs responded to the survey. The total number of currently open staffed ICU beds was 2183. This was 195 fewer (8.2%) than in 2020; the decline was greater for rural/regional (18%) and private ICUs (18%). The reported maximal ICU bed capacity (5623) included 813 additional physical ICU bed spaces and 2627 in surge areas outside ICUs. The number of available ventilators (7196) exceeded the maximum number of ICU beds. The reported number of available additional nursing staff would facilitate the immediate opening of 383 additional physical ICU beds (47%), but not the additional bed spaces outside ICUs. Conclusions: The number of currently available staffed ICU beds is lower than in 2020. Equipment shortfalls have been remediated, with sufficient ventilators to equip every ICU bed. ICU capacity can be increased in response to demand, but is constrained by the availability of appropriately trained staff. Fewer than half the potentially additional physical ICU beds could be opened with currently available staff numbers while maintaining pre‐pandemic models of care.